THE SECRETORY STRUCTURE OF ESSENTIAL OILS IN SOME SPECIES OF LAMIACEAE FOR TRADITIONAL COSMETICS OF BESEMAH TRIBES LAHAT’S DISTRICT - Tanzerina, Nina; Aminasih, Nita; -, Erliah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
Besemah tribe uses plants in addition to the treatment is also used for beauty treatments traditionally. Based on Agustina's (2015) study, 109 species of plants were used for traditional medicine by the Tribe of Besemah. Some species of Lamiaceae for traditional medicine such as patchouli (Pogostemon cablin (Blanco) Benth.), wild mint (Mentha arvensis L.), hoary basil (Ocimum americanum L.), mexican mint (Plectranthus amboinicus (Lour.) Spreng.), and sweet basil (Ocimum basilicum L.) contains essential oils that can be used for traditional cosmetic ingredients. Essential oils are stored in the secretory structure of plants in leaf and stem organs. This study aims to determine the type and location of the secretory structure of essential oils in some species of lamiaceae used for traditional cosmetics of Besemah Tribes Lahatâ€™s District. The research was conducted in November 2016 until February 2017. The results showed that patchouli plants was found in the presence of glandular trichomes, oil cells, and idioblast cells. The wild mint plants have glandular trichomes. The hoary basil plants have glandular trichomes and oil cells. The mexican mint plants have glandular trichomes and idioblast cells. The sweet basil plants have glandulartrichomes.Keywords: essential oils, lamiaceae, traditional cosmetics, Besemah tribes,Â glandular trichomes, oil cells, idioblast cells